Hospital Mortality and Trainee Experiences: How General Medical Council Survey Findings Correlate With Summary Hospital-Level Mortality Indicator. Issue 2 (27th March 2023) - Barton, Jack Charles; Richardson, Daniel; Corrigan, Amber Elyse; Kuri, Ashvin; Round, Jonathan
Abstract : Objectives: This study aimed to investigate whether components of junior doctor satisfaction are associated with patient mortality within the United Kingdom. Methods: We conducted a cross-sectional study of publicly available data (the General Medical Council [GMC] National Survey and the Summary Hospital-level Mortality Indicator [SHMI]) pertaining to subjective physician trainee satisfaction and patient mortality within 80 United Kingdom–based healthcare institutions. The direction and strength of correlation between components of the GMC National Survey and relative patient mortality as described by the SHMI were calculated. Additional outcomes included mean GMC survey scores for reported domains and mean SHMI by healthcare institution. Results: SHMI for included healthcare institutions ranged from 0.69 to 1.21 (mean [SD], 1.01 [0.1]). Mean GMC domain scores ranged between 44.61 and 88.62 (mean [SD], 71.16 [10.84]). Statistically significant correlations were observed for clinical supervision, clinical supervision out of hours, rota design, overall satisfaction, and teamwork. After application of Bonferroni correction, statistically significant correlations remained for both clinical supervision and clinical supervision out of hours. Conclusions: There is a significant association between components of subjective trainee satisfaction and patient mortality within the United Kingdom. Further investigation to examine these relationships, perhaps to target intervention, may prevent avoidable patient harm.